Route Optimization of Stacker in Automatic Warehouse Based on Genetic Algorithm - Cui Changqing; Wang Yiqiang (Institute of Advanced Engineering and Science, 2013)
Today, automatic warehouse system gradually replaced manual labor, and played an important role in the production work, especially in the cargo handling work. It was important to research the time-consuming and efficiency of stacker in the automated warehouse system. This paper researched the path of stacker in automated warehouse and calculated the operation time of stacker working path according to actual working condition, and then put forward a route optimization method of stacker based on genetic algorithm, finally simulated this algorithm by using MATLAB. The simulation results showed that this algorithm could shorten the way of stacker, and increase the working efficiency of the warehouse. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.2959